TERJEBAK DALAM MEDIA SOSIAL: STUDI TENTANG PERILAKU MAHASISWA SOSIOLOGI UNIVERSITAS NEGERI MAKASSAR DI MEDIA SOSIAL - Basri, Achmad Syafiyullah; Abdullah, Suparman; A.T., M. Ramli (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
Information technology has grown rapidly, this was accompanied by changes that were present behind it. This study aims to unravel the problems faced by Sociology students at Makassar State University, namely the phenomenon of being trapped on social media. Qualitative research methods are used to unravel the changes that arise because of social media, purposive sampling was used to determine the quality of the informants to be interviewed, documentation guarantees the authenticity of the information and data contained in the document, and library studies are used to add references to similar problems. The conclusions from the results of this study indicate the form of entrapment of informants on social media as follows: with high access and activity on social media, the habit of making the media as a source of information is full of hoaxes, there is a change in consumption activities by online game user informants, namely the consumption of pseudo commodities that have a lot of risk. In the end this study presents the contemporary reality of information behavior on social media that influences its social relations.